2002
DOI: 10.1093/carcin/23.4.559
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of the imprinted NNAT locus occurs frequently in pediatric acute leukemia

Abstract: Recent studies have demonstrated imprinting of the human neuronatin (NNAT) gene. NNAT maps to 20q11.2-q12, a region exhibiting loss of heterozygosity in acute myeloid leukemia and myelodysplastic/myeloproliferative disease. To investigate possible epigenetic dysregulation of genes in this region relevant to leukemogenesis, we analyzed methylation of the NNAT gene in normal tissues and in leukemias. We found a differential methylation pattern, typical of imprinted genes, at sites in the CpG island containing NN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…Indeed, and in this context, decreased Nnat expression was identified in a screening study of rat cells in the progression from immortalization to transformation (Yoshioka et al 2000). Although this study did not report the functional significance of Nnat loss in this transition, other studies of different tumour types have shown that NNAT may exhibit either a tumour suppressing or in some cases a tumour promoting role (Takeuchi et al 1995, Asimakopoulos et al 1996, Usui et al 1997, Hu et al 2002, Kuerbitz et al 2002, Wood et al 2002, Becker et al 2005, Zhong et al 2006.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Indeed, and in this context, decreased Nnat expression was identified in a screening study of rat cells in the progression from immortalization to transformation (Yoshioka et al 2000). Although this study did not report the functional significance of Nnat loss in this transition, other studies of different tumour types have shown that NNAT may exhibit either a tumour suppressing or in some cases a tumour promoting role (Takeuchi et al 1995, Asimakopoulos et al 1996, Usui et al 1997, Hu et al 2002, Kuerbitz et al 2002, Wood et al 2002, Becker et al 2005, Zhong et al 2006.…”
Section: Introductionmentioning
confidence: 84%
“…Genome-wide identification of genes silenced through epigenetic mechanisms, and in particular through CpG island methylation, has been investigated in multiple different tumour types (Kuerbitz et al 2002, Liang et al 2002, Suzuki et al 2002, Foltz et al 2006, Ibanez de Caceres et al 2006. These studies frequently employ pharmacological strategies to 'unmask' silent genes through inhibition of the DNA maintenance methylase enzyme, DNMT1.…”
Section: Endocrine-related Cancermentioning
confidence: 99%
“…Indeed, ectopic expression of NNAT stimulated 3T3-L1 adipocytes to differentiate into mature adipocytes by increasing intracellular calcium levels and enhancing cAMP-responsive element-binding protein (CREB) phosphorylation (Suh et al, 2005). NNAT was found to undergo LOI in 69% of leukemia samples in one study, although its effects on cell growth were not analysed (Kuerbitz et al, 2002). LOI of NNAT in 20% of the adjacent normal tissues we examined suggests that this may represent a preneoplastic alteration, as has been observed for other imprinted genes like IGF2 in colon cancer (Cui et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Gas6 and Ocm have oncogenic functions (41,42). Nnat is known as an imprinting gene and its aberrant hypermethylation occurs frequently in pediatric acute leukemia (43). There is a possibility that silencing of these genes is related to the development and progression of rat prostate carcinoma.…”
Section: Discussionmentioning
confidence: 99%